Studi Mengenai Loyalitas Pelanggan Jasa Transportasi Bus Dengan Kepuasan Pelanggan Sebagai Variabel Mediasi - Prida Najwa Azzahra; Sri Rahayu Tri Astuti (Diponegoro Journal of Management, 2025)
Lifestyle changes and increasing public demands for better services in transportation growth are challenges in maintaining customer loyalty. Tight competition, negative reviews, and issues such as accidents that can affect brand image. This study applies the Theory of Planned Behavior (TPB) as a theoretical approach that aims to understand how service quality, customer experience, and brand image affect customer loyalty, with customer satisfaction as a mediating variable. By using quantitative methods.Literature studies are applied to obtain relevant data and information and the use of questionnaires as instruments in obtaining data through a series of questions designed to collect information from respondents and then analyzed using Structural Equation Modeling (SEM) analysis techniques with AMOS 22 software. The sample size used was 130 respondents by customers who had used the PO Bus Rosalia Indah service more than once in the past year in Semarang City.The results showed that customer satisfaction had a positive effect on customer loyalty, mediating the influence of service quality, customer experience, and brand image on customer loyalty. These findings indicate that to increase customer loyalty, PO Bus Rosalia Indah must focus on improving service quality, creating positive customer experiences, and strengthening brand image.